Analisis Kualitas Pelayanan Pendaftaran Rawat Jalan Di RSUD Besemah Kota Pagar Alam Tahun 2021 - Ipana Jayanti; Lilis Suryani; Dian Eka Anggreny (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
Quality of service is the best service provided to patients, so that the service felt by patients is of quality so that patients feel satisfied with the services provided. This study aims to determine the quality of outpatient registration services at Besemah Hospital, Pagar Alam City in 2021. The location of this research is the outpatient registration at Besemah Hospital, Pagar Alam City in 2021. This study is a quantitative study with a cross sectional design. The sample in this study were patients who visited the outpatient polyclinic of RSUD Basemah totaling 100 respondents who were selected using purposive sampling technique. The data in this study were obtained using a questionnaire instrument, then analyzed using the chi square test dan logistic regression. This research was carried out in June 2021 at Basemah Hospital, Pagar Alam City. The results of data analysis showed that there was a relationship between responsiveness, reliability, assurance dan empathy with a value (p < 0.05). Dominant factors on service quality are Empathy, Reliability dan assurance It is hoped that the hospital will improve outpatient services with an integrated registration system in the system, because there are still patient registration queues so it takes a long time for patients to register.